Domain-swapping analysis of FtsI, FtsL, and FtsQ, bitopic membrane proteins essential for cell division in Escherichia coli. - Guzman, L M (1997)
FtsI, FtsL, and FtsQ are three membrane proteins required for assembly of the division septum in the bacterium Escherichia coli. Cells lacking any of these three proteins form long, aseptate filaments that eventually lyse. FtsI, FtsL, and FtsQ are not homologous but have similar overall structures: a small cytoplasmic domain, a single membrane-spanning segment (MSS), and a large periplasmic domain that probably encodes the primary functional activities of these proteins. The periplasmic domain of FtsI catalyzes transpeptidation and is involved in the synthesis of septal peptidoglycan. The precise functions of FtsL and FtsQ are not known. To ask whether the cytoplasmic domain and MSS of each protein serve only as a membrane anchor or have instead a more sophisticated function, we have used molecular genetic techniques to swap these domains among the three Fts proteins and one membrane protein not involved in cell division, MalF. In the cases of FtsI and FtsL, replacement of the cytoplasmic domain and/or MSS resulted in the loss of the ability to support cell division. For FtsQ, MSS swaps supported cell division but cytoplasmic domain swaps did not. We discuss several potential interpretations of these results, including that the essential domains of FtsI, FtsL, and FtsQ have a role in regulating the localization and/or activity of these proteins to ensure that septum formation occurs at the right place in the cell and at the right time during the division cycle.